The International Society of Nephrology Collaborative Quality Framework to Support Safe and Effective Dialysis Provision in Resource-Challenged Settings - Simon Davies; Saraladevi Naicker; Adrian Liew; Tushar Vachharajani; Roberto Pecoits-Filho; Vivekanand Jha; Fredric Finkelstein; David C.H. Harris (Kidney International Reports)
Global underprovision of affordable dialysis results in inequitable access to safe and effective treatment. The need for a dialysis quality framework that would set minimum standards for safe and effective treatment, was identified as a key priority for the International Society of Nephrology (ISN) Kidney Failure Strategy. In addition, this framework, which was developed through collaboration and iterative review to ensure external validity, links these standards to resource requirements and suggested reporting tools. The framework includes elements that are designed to minimize catastrophic health care expenditure, by mandating transparent individualized affordable dialysis planning and encourages continuous quality improvement by including a tiered approach to standards. Although a set of minimum mandatory standards is included with a strong focus on patient safety, this is not intended as a goal for all, but to support the incremental development of dialysis in the most challenging resource settings. Providers and funders are expected to engage with the framework at a level commensurate with their resources, clearly identifying the area where lack of resource is leading to suboptimal quality. In this way, the framework empowers policy makers, health care commissioners, and patient groups to work with providers to ensure quality and meet demand.